Laparoscopic resection of pheochromocytoma (paraganglioma) of the organ of Zuckerkandl in a pediatric patient - Katherine Kramme; Robin Fountain; Michael Leinwand (Elsevier, 2022)
Background: Pheochromocytoma is a rare neuroendocrine tumor that secretes catecholamines. Classically located in the adrenal gland, a small percentage of pheochromocytomas arise along the sympathetic chain. The majority of cases are diagnosed among adults age 20-50 years old. Laparoscopic adrenalectomy has become standard treatment for pheochromocytoma of the adrenal gland. The safety and efficacy of laparoscopic approach to resection of extra-adrenal pheochromocytoma in the pediatric population has not been established. Discussion: We present an interesting case of a 12-year-old female diagnosed with a functional pheochromocytoma of the Organ of Zuckerkandl. Following preoperative optimization of blood pressure, she underwent successful tumor resection via a minimally invasive laparoscopic approach. The operation was completed without intraoperative complication. She was discharged home the following day with resolution of symptoms. She continues to do well in follow up. Conclusion: We demonstrate the successful laparoscopic resection of pheochromocytoma localized to the Organ of Zuckerkandl in a pediatric patient.